Inovasi Penggunaan Limbah Ampas Kopi untuk Meningkatkan Hasil Biogas: Studi Eksperimental terhadap Emisi CH₄ dan CO₂ - Regita Bellatrix , Angelica; Crisanto Putra Mbulu, Bernardus (PROTON, 2025)
Biogas is a widely recognized alternative energy source among Indonesian communities. It is produced through the anaerobic fermentation of livestock manure and water, and can be combined with other organic waste materials to enhance gas production. The addition of organic waste in biogas production has been shown to significantly influence the quantity and quality of the resulting gas output. Therefore, this research was conducted by introducing coffee dreg waste into the process to evaluate its effect on the production of methane (CH₄) and carbon dioxide (CO₂), using MQ-4 and MQ-135 gas sensors for detection. Data analysis revealed that the chemical components present in the added coffee dregs effectively increased the reaction rate during biogas production. This was demonstrated by the highest methane concentration achieved by the specimen with the largest coffee dreg content (444), reaching 247.033 ppm. Meanwhile, the highest carbon dioxide concentration was obtained from the specimen with a smaller amount of coffee dreg addition (441), measuring 141.202 ppm.